Stability of blood‐based biomarkers of Alzheimer's disease over multiple freeze‐thaw cycles. Issue 1 (3rd July 2018) - Keshavan, Ashvini; Heslegrave, Amanda; Zetterberg, Henrik; Schott, Jonathan M.
Abstract: Introduction: Freeze‐thaw instability may contribute to preanalytical variation in blood‐based biomarker studies. We investigated the effects of up to four freeze‐thaw cycles on single molecule array immunoassays of serum neurofilament light chain and plasma total tau, amyloid β 1–40 (Aß40 ), and Aβ 1–42 (Aβ42 ). Methods: Individuals who had peripheral venepuncture during investigation of suspected neurodegenerative disease were recruited. After standardized preprocessing, 200 μL of plasma and serum aliquots were stored at −80°C within 60 minutes. Aliquots underwent one to four freeze‐thaw cycles. Results: There was no significant difference across four freeze‐thaw cycles for serum neurofilament light chain (n = 12), plasma total tau (n = 11), or plasma Aβ42 (n = 12). For plasma Aβ40 (n = 14), there were significant median reductions by ratios of .96 and .92 at the third and fourth cycles, respectively. Discussion: Up to four freeze‐thaw cycles do not influence single molecule array blood biomarkers of neurofilament light chain, total tau, or Aβ42, with at most minor reductions in Aβ40 .